2022
DOI: 10.3390/plants11070870
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Anatomy of Three Native Species of Tillandsia L. from the Atacama Desert, Chile

Abstract: In the extreme north of Chile, the genus Tillandsia L. (Bromeliaceae) is represented by three native species, T. marconae Till & Vitek and T. landbeckii Phil., both of terrestrial atmospheric habit, and T. virescens Ruiz & Pav. of saxicolous habit. There is little information on the foliar structures that allow its establishment in arid environments. Therefore, we studied the leaf anatomy of each of these terrestrial and saxicolous atmospheric species from different altitudinal levels (1000 and 3000 m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Studies have generally focused on the adaxial surfaces of leaves; however, it was suggested in studies carried out on V. vinifera , V. davidii (Rom. Caill) Föex., and V. doaniana Munson [ 37 ] that trichomes on the abaxial surface might be as important as the adaxial surfaces as they may provide canopies to shield the leaf surface from destructive ultraviolet rays [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have generally focused on the adaxial surfaces of leaves; however, it was suggested in studies carried out on V. vinifera , V. davidii (Rom. Caill) Föex., and V. doaniana Munson [ 37 ] that trichomes on the abaxial surface might be as important as the adaxial surfaces as they may provide canopies to shield the leaf surface from destructive ultraviolet rays [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…1C) [28,34]. They obtain fog water by waterabsorbing trichomes, which cover their leaves, rather than by functional roots, which are usually lacking [33,35,36]. Nutrients such as nitrogen are considered to be also largely fog supplied [37,38], whereas the lower parts of the shoots are usually buried under sandy substrate, therewith supporting anchorage [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, leaf acclimatization and adaptations have historically been used as indicators of environmental conditions (Rosas et al, 2021). Due to the external morphology and the anatomy of leaves often have traits for protection and control of water loss that are fundamental to plant survival (Méndez‐Alonzo et al, 2012; Melo Júnior and Torres Boeger, 2015; de Paula et al, 2019; Bona et al, 2020; Belmonte et al, 2022). In contrast, the secondary xylem has a longer‐term function and thus represents responses integrated over longer times.…”
mentioning
confidence: 99%